Foreign language learning In-Tandem: Teletandem as an alternative proposal in CALLT1 - João A. Telles; Maria Luisa Vassalo (The ESPecialist: Research in Language for Specific Purposes, 2011)
In a previous paper on this journal (Vassallo & Telles, 2006), we presented the theoretical bases and practical procedures of two modes of foreign language learning in-tandem approach – face-to-face tandem and e-tandem. Now, in this article, we introduce our proposal of a third mode of Tandem – the Teletandem, as an alternative in CALLT. Teletandem is a virtual Tandem that uses the online writing, reading, audio and video resources of the Windows Live Messenger. Next, we wish to outline and to argue for the applicability of the theoretical and practical principles of this third mode of Tandem within the context of a research project – Teletandem Brasil: Foreign languages for all. One of the central aims of this project is to promote, by means of the virtual space of the Teletandem, the contact of Brazilian university students with the peoples of the international community and the exchange of their respective languages and cultures.